2024
DOI: 10.3390/agronomy14010143
|View full text |Cite
|
Sign up to set email alerts
|

Swine Wastewater Treatment System Using Constructed Wetlands Connected in Series

Amalia García-Valero,
José Alberto Acosta,
Ángel Faz
et al.

Abstract: The main objective of this study was to analyze the efficiency of CWs for purifying swine wastewater in order to reduce its pollutant load. The system included a pretreatment module (raw swine wastewater tank, phase separator, and settlement tank), and three constructed wetlands connected in series and planted with Phragmites australis and Suaeda vera. Three treatment cycles were carried out with a total hydraulic retention time in the wetland of 21 days for each cycle. Pig slurry samples were collected in tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…K is highly mobile in soil and can be easily leached [48,53,54]. Previous studies have reported high amounts of K in the leachate from treatments with high doses of SWW [56,57]. On the other hand, K can also be fixed in interlayers of primary or secondary minerals in the soil, serving as reservoirs, with the fixation release dynamics controlled by the addition (i.e., fertilizers) or exhaustion (i.e., plant uptake) of the mineral in the soil solution (i.e., exchangeable K + ), pH, CEC, and other environmental factors [58].…”
Section: Discussionmentioning
confidence: 99%
“…K is highly mobile in soil and can be easily leached [48,53,54]. Previous studies have reported high amounts of K in the leachate from treatments with high doses of SWW [56,57]. On the other hand, K can also be fixed in interlayers of primary or secondary minerals in the soil, serving as reservoirs, with the fixation release dynamics controlled by the addition (i.e., fertilizers) or exhaustion (i.e., plant uptake) of the mineral in the soil solution (i.e., exchangeable K + ), pH, CEC, and other environmental factors [58].…”
Section: Discussionmentioning
confidence: 99%